Prediction of Lifetime for Different Asphalt Concrete Mixes - Öngel, Aybike; Harvey, John (Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxon, England, 2012)
The California Department of Transportation has been using open-graded mixes to reduce traffic noise levels and to improve wet weather safety. There is a need to identify how long open-graded mixes last in terms of permeability, skid resistance, roughness, and noise reduction and to compare their lifetime with other asphaltic mixes. In 2005, Caltrans initiated a long-term program to investigate and monitor field performance of different asphalt concrete mixes. A total of 72 field pavement sections with different asphalt mix surfaces that were at that time less than 8 years old were included in the study. Regression models were developed for performance variables of permeability, skid resistance, roughness, and noise. The lifetimes for different asphalt concrete mixes under different traffic and climatic conditions were estimated.
Keywords: pavement/tire noise; friction; permeability; IRI; kaldırım / lastik sesi; sürtünme; geçirgenlik